A Stack Bonded Thermo-Pneumatic Micro-Pump Utilizing Polyimide Based Actuator Membrane For Biomedical Applications - Norihan, Abdul Hamid; Majlis, Burhanuddin Yeop; Yunas, Jumril; Ahmad Radzi, Syafeeza; Wong, Yan Chiew; Ibrahim , Mazree (SPRINGER, 2016)
-